Therapeutic Potential of (−)-Agelamide D, a Diterpene Alkaloid from the Marine Sponge Agelas sp., as a Natural Radiosensitizer in Hepatocellular Carcinoma Models - Choi, Changhoon (Mar Drugs, 2020)
Radiation therapy (RT) is an effective local treatment for unresectable hepatocellular carcinoma (HCC), but there are currently no predictive biomarkers to guide treatment decision for RT or adjuvant systemic drugs to be combined with RT for HCC patients. Previously, we reported that extracts of the marine sponge Agelas sp. may contain a natural radiosensitizer for HCC treatment. In this study, we isolated (−)-agelamide D from Agelas extract and investigated the mechanism underlying its radiosensitization. (−)-Agelamide D enhanced radiation sensitivity of Hep3B cells with decreased clonogenic survival and increased apoptotic cell death. Furthermore, (−)-agelamide D increased the expression of protein kinase RNA-like endoplasmic reticulum kinase/inositol-requiring enzyme 1α/activating transcription factor 4 (PERK/eIF2α/ATF4), a key pathway of the unfolded protein response (UPR) in multiple HCC cell lines, and augmented radiation-induced UPR signaling. In vivo xenograft experiments confirmed that (−)-agelamide D enhanced tumor growth inhibition by radiation without systemic toxicity. Immunohistochemistry results showed that (−)-agelamide D further increased radiation-induced ATF4 expression and apoptotic cell death, which was consistent with our in vitro finding. Collectively, our results provide preclinical evidence that the use of UPR inducers such as (−)-agelamide D may enhance the efficacy of RT in HCC management.